PERAN GREEN TRUST DALAM MEMEDIASI PENGARUH GREEN PERCEIVED VALUE TERHADAP GREEN PURCHASE BEHAVIOR - I Putu Agus Surya Setiawan; Alit Suryani (Faculty of Economics and Business Udayana University, 2016)
The purpose of this study is to analyze the effect of green perceived value on green purchase behavior and therole of green trust in mediating the relationship between the two variables. The population of this study wasconsumer of organic product in Denpasar City. The sampling method used was purposive sampling with 110respondents. Analysis technique used was path analysis and Sobel Test. The results show that gren perceivedvalue positively affect green purchase behavior and green trust was positively mediates the effects of greenperceived value on green purchase behavior of organic products. It is recommended to the marketer oforganic products to inform the comunity about the benefits of consuming organic products. additionally,farmer of organic products is expected to maintain the quality of their product.